2009
DOI: 10.1038/nature08628
|View full text |Cite
|
Sign up to set email alerts
|

Secreted semaphorins control spine distribution and morphogenesis in the postnatal CNS

Abstract: The majority of excitatory synapses in the mammalian CNS are formed on dendritic spines1, and spine morphology and distribution are critical for synaptic transmission2–6, synaptic integration and plasticity7. Here, we show that a secreted semaphorin, Sema3F, is a negative regulator of spine development and synaptic structure. Mice with null mutations in genes encoding Sema3F, and its holoreceptor components neuropilin-2 (Npn-2) and plexinA3 (PlexA3), exhibit increased dentate gyrus (DG) granule cell (GC) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
313
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(344 citation statements)
references
References 24 publications
31
313
0
Order By: Relevance
“…Indeed, NRP1 was observed on basal and apical dendritic processes at 18DIV of primary mouse cortical neurons from E14.5 mouse embryos. 27 Aberrant dendritic or spine morphology and spine density in P21 and adult DG GCs of NRPs and PlexAs mutant mice further support the role of these dendritic semaphorin receptors in dendritic branching and spine morphogenesis. Sema3A may be secreted from non-neuronal cells such as astrocytes and smooth muscle cells as well as pre-and/or postsynaptic neurons.…”
Section: Sema3a Regulates Dendritic Localization Of Ampa Glutamate Rementioning
confidence: 84%
See 4 more Smart Citations
“…Indeed, NRP1 was observed on basal and apical dendritic processes at 18DIV of primary mouse cortical neurons from E14.5 mouse embryos. 27 Aberrant dendritic or spine morphology and spine density in P21 and adult DG GCs of NRPs and PlexAs mutant mice further support the role of these dendritic semaphorin receptors in dendritic branching and spine morphogenesis. Sema3A may be secreted from non-neuronal cells such as astrocytes and smooth muscle cells as well as pre-and/or postsynaptic neurons.…”
Section: Sema3a Regulates Dendritic Localization Of Ampa Glutamate Rementioning
confidence: 84%
“…However, Tran et al reported that the Sema3A signaling did not influence spine morphogenesis or distribution. 27 The Golgi-labeled Nrp1 Sema¡ and Sema3A ¡ / ¡ mouse brains did not exhibit spine density defects along apical dendrites of cortical layer V neurons. In addition, analysis of adult PlexA3 ¡ / ¡ and PlexA4 ¡ / ¡ mutant brains revealed that apical dendrite spine morphology was not altered in PlexA4 ¡ / ¡ .…”
Section: Background: Dendritic Development Regulated By Semaphorinsmentioning
confidence: 86%
See 3 more Smart Citations